MENINGKATKAN KETERLIBATAN SISWA MENGGUNAKAN ONLINE STUDENT RESPONSE SYSTEM : EKSPERIMEN - Binti Lathifaturrohmah AJ; Nur Anita Yunikawati (Balai Besar Guru Penggerak Jawa Timur, 2022)
Low student engagement can be indicated by students who are passive during learning, are not interested in learning and lack of focus on learning. This can be addressed by the use of OSRS(Socrative and Clickers) to increase student engagement. The purpose of this study was to determine the influence and differences in student engagement between classes that use Socrative and classes that use Clickers. The